1990
DOI: 10.1063/1.459699
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium kinetics of the reaction H+Br2 in xenon within a Lorentz gas model

Abstract: The reaction H+Br2→products in the carrier gas xenon is studied in the framework of the Lorentz gas model. The nonequilibrium velocity distribution function fH of the light component H is calculated from the Lorentz–Fokker–Planck equation. This permits the determination of the nonequilibrium temperature TH and the nonequilibrium rate coefficient k of this reaction. These kinetic quantities are numerically calculated and compared with various other approaches for solutions of the appropriate Boltzmann equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This expansion has been adopted in several papers, see for example [2,7,13,16,20], in contrast to some others in which the first-order expansion is considered, see for example [15,23]. The truncation at the second order does not seem to represent a relevant limitation, since the expansion is capable to reproduce an appreciate effect of the reaction heat on the distribution function.…”
Section: The Distribution Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expansion has been adopted in several papers, see for example [2,7,13,16,20], in contrast to some others in which the first-order expansion is considered, see for example [15,23]. The truncation at the second order does not seem to represent a relevant limitation, since the expansion is capable to reproduce an appreciate effect of the reaction heat on the distribution function.…”
Section: The Distribution Functionmentioning
confidence: 99%
“…After the pioneering papers by Prigogine and collaborators [1,2], and further works by Present [3] and Ross and Mazur [4], several authors have studied the description of non-equilibrium flows with the aim of investigating molecular transport of chemically reactive systems. The theoretical treatment of most papers involves the Chapman-Enskog method [1]- [3], [5]- [16], numerical approaches related to the Monte Carlo method [17]- [20], molecular dynamics simulations [21,22] and analysis of non-equilibrium effects [13], [23]- [27]. Other main papers for the kinetic theory of reacting gases up to 1994 can be found in the extensive bibliography compiled by Kennedy [28].…”
Section: Introductionmentioning
confidence: 99%
“…Introducing an additional term in the perturbation solution of the Boltzmann equation we have shown [23] that the nonequilibrium effect on the rate constant of chemical reaction can be much larger than in Refs. [5][6][7][8] and that similarly as in the Lorentz gas [10][11] the results are accurate for slow reactions only. These results [23] have been also confirmed by the molecular dynamics simulation method developed by Gorecki [24][25][26].…”
Section: Introductionmentioning
confidence: 67%
“…That is why, recently other possibilities of verification of the results obtained by the perturbation method in this case have been used. Namely, for chemical reaction proceeding in the Lorentz gas, reasonable comparison between such results and the results obtained from the exact numerical solution of the Fokker-Planck equation [10][11][12] has been performed. We also decided to compare the results obtained from the perturbation solution for the bimolecular chemical reaction in the dilute gas with the results from the Monte Carlo computer simulations of solution of the Boltzmann equation for this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In this condition, the particle velocity distribution function is assumed to maintain a Maxwellian shape during the evolution of the effective temperature of the system at a rate imposed by chemistry and exchanges at the boundaries. However, kinetic theory studies based on the Boltzmann equation have revealed that a chemical reaction may induce a departure from partial equilibrium and influence the dynamics of gaseous chemical systems [4][5][6][7][8][9][10][11][12][13]. Indeed, the reactivity of a molecule depends on its kinetic energy.…”
Section: Introductionmentioning
confidence: 98%